Statistical power analysis for the behavioral sciences - Cohen, Jacob, 1923-1998 (Academic Press, 1977)
Statistical Power Analysis for the Behavioral Sciences, Revised Edition emphasizes the importance of statistical power analysis. This edition discusses the concepts and types of power analysis, t test for means, significance of a product moment rs, and differences between correlation coefficients. The test that a proportion is .50 and sign test, differences between proportions, and chi-square tests for goodness of fit and contingency tables are also elaborated. This text likewise covers the F tests of variance proportions in multiple regression/correlation analysis and computational procedures. This publication is intended for behavioral and biosocial scientists who use statistical inference, but also serves as a supplementary textbook for intermediate level courses in applied statistics in behavioral/biosocial science.